The effect of gender and language proficiency on the metaphor use in the writing of TEFL students - Nazila Fattahi (SpringerOpen, 2021)
Abstract The ubiquitous nature of metaphor in everyday life and its significance in second language learning has triggered plethoric research on the relationship between metaphor and language learning. To contribute to the still growing literature, the current study explore the effect of learner variables, namely gender and proficiency, on metaphor use in TEFL students’ writing. To achieve that objective, 27 intermediate and 23 upper-intermediate Iranian TEFL students were asked to write on an IELTS Writing Task 2 topic. Fifty essays were analyzed for metaphor use through Metaphor Identification Procedure (Pragglejaz Group in Metaphor Symb 22(1):1–39, 2007) and Vehicle Identification Procedure (Cameron in Metaphor in educational discourse, Continuum, London, 2003). The data analyzed through t-test and multiple regression analysis revealed the advantage of upper-intermediate students over intermediate students concerning metaphor use in their writing. Gender, on the other hand, did not play an influential role in the students’ metaphor use. The findings of this research and the implications they might have for the field of English language teaching will be discussed.